Study on the Ideological and Political Practice Teaching of College Students Based on the Internet + Technology - Zeng, Ji; Sutummawong, Nantida (International Journal of Informatics and Information Systems, 2023)
At present, although the ideological and political courses in Colleges anduniversities include practical teaching, there are many problems in practical teaching. Therefore, the reform of College Students' Ideological and political practice teachingmode has become a key research issue. Through the practical teaching mode, wecanenhance the attraction of Ideological and political course, which will improvetheteaching effect. This paper first analysis the importance of practical teachingintheideological and political course. Then, this paper puts forward some problems inpractical teaching. Finally, some suggestions are put forward.